Pengembangan Desain Kompor Gasifikasi Top Lith Up Draft (TLUD) - Syahrir, Muhamad Ashar; Mangalla, Lukas Kano; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
The use of environmentally friendly stoves in the household sector can be an alternative to overcome the limited use of kerosene and the constrained supply of LPG. The purpose of the study was to develop a gasification stove design with the concept of Top Lith Up Draft on several variations of the column, namely without columns, column 2 holes and column 4 holes using cashew shell fuel which produces optimal gas fuel. The research method is the Top Lith Up Draft method, which is a gasification process semi-gasifier technology method that can produce fewer emissions that can harm human health. The results obtained indicate that the development of the TLUD gasification stove design from several variations of the column functions well. The gasification testing process carried out for the three variations of the column used resulted in good temperature values, namely for variations without a temperature column of 829 , column 2 holes of 935 , and column 4 holes of 934 . The best column variation is the 2 hole column with the highest temperature value of 935. Kata kunci: Gasification, TLUD, cashew shell,  efficiency.